Specific Histopathologic Features Aid in Distinguishing Diffuse-type Gastric Adenocarcinoma From Metastatic Lobular Breast Carcinoma. (January 2020) - Clinton, Lani K.; Plesec, Thomas; Goldblum, John R.; Hajifathalian, Kaveh; Downs-Kelly, Erinn; Patil, Deepa T.
Abstract : Metastatic invasive lobular carcinoma (mILC) may masquerade as primary diffuse gastric adenocarcinoma (PDGA) by demonstrating significant clinical and pathologic overlap. Accurate distinction is of therapeutic and prognostic significance. On the basis of anecdotal cases of mILC that lacked estrogen receptor and/or GATA3 expression, we analyzed the cytoarchitectural features of 28 mILC and 44 PDGA specimens obtained from women to assess features that would help in this distinction and prompt ancillary work-up. In addition to performing an interobserver agreement analysis among 3 pathologists, we also evaluated SATB2 expression in this setting. Eighteen of 20 (90%) patients had a history of ILC. The mean interval between initial diagnosis of breast cancer and metastasis was 7.3 years (range: 1 to 36 y). Compared with mILC, PDGA was significantly associated with full-thickness mucosal involvement (47% vs. 80%; P =0.015), a nested/sheet-like growth pattern (32% vs. 68%; P =0.004), anastomosing cords (0% vs. 100%; P =0.001), multivacuolated cells (0% vs. 61%; P <0.0001), pleomorphic nuclei (4% vs. 70%; P <0.0001) and enlarged nuclei (4% vs. 70%; P <0.0001). Single file growth pattern ( P <0.0001) and superficial lamina propria involvement ( P =0.009) were more common in mILC. Estrogen receptor and GATA3 were expressed in all but 5 mILC cases; SATB2 was only seen in 30% of PDGA cases. Our results demonstrate that in a biopsy specimen, careful morphologic assessment can be extremely helpful in distinguishing mILC from PDGA and guiding ancillary work-up, especially when a history of breast cancer may not be readily available or when the neoplasm lacks expression of conventional breast markers.